1993
DOI: 10.1002/ldr.3400040415
|View full text |Cite
|
Sign up to set email alerts
|

Potential chemical time bombs in the schelde estuary

Abstract: The Schelde estuary is heavily polluted with many different (micro)pollutants. This results in high concentrations in the abiotic and biotic compartments of the Schelde estuary and in various effects. The present day suboxic and anoxic conditions in the upper estuary are probably responsible for the high distribution coefficients for some trace metals in the lower Schelde estuary (Western Schelde). A future reduction in discharges with a high biological oxygen demand will therefore not only result in higher ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
1
3
0
2
Order By: Relevance
“…According to the correlation analysis among the partition coefficients of heavy metals and the environmental parameters, we could deduce that high primary production could cause Fe and Pb to be more easily partitioned into the particulate phase and could cause Cu and Cd to be more easily partitioned into the dissolved phase. Similar conclusions were also obtained in other studies [ 3 , 8 , 54 ]. Similar with Fe and Pb to some extent, high concentrations of Chl a , DO and high pH were favorable for the partitioning of Mn and Zn to into the particulate phase.…”
Section: Discussionsupporting
confidence: 93%
“…According to the correlation analysis among the partition coefficients of heavy metals and the environmental parameters, we could deduce that high primary production could cause Fe and Pb to be more easily partitioned into the particulate phase and could cause Cu and Cd to be more easily partitioned into the dissolved phase. Similar conclusions were also obtained in other studies [ 3 , 8 , 54 ]. Similar with Fe and Pb to some extent, high concentrations of Chl a , DO and high pH were favorable for the partitioning of Mn and Zn to into the particulate phase.…”
Section: Discussionsupporting
confidence: 93%
“…In relation to chemical speciation, studies have shown that the distribution of heavy metals is strongly influenced by salinity, dissolved organic carbon and dissolved oxygen in the WS (i.e. Van Eck & De Rooij, 1993;Paucot & Wollast, 1997;Zwolsman et al, 1997;Gerringa et al, 1998). In spring when the freshwater inflow in the estuary is largely anoxic, dissolved metal concentrations tend to be very low especially in the upper estuary and metal partitioning in those conditions favours adsorption to suspended particles and sediments.…”
Section: Tissue Metal Concentration (µG/g)mentioning
confidence: 98%
“…The Schelde Estuary is one of the larger north-west European estuaries with a complete salinity gradient, including a large freshwater tidal area. Especially the part between the Dutch^Belgian border and the Rupel is severely impacted and heavily polluted by domestic, industrial and agricultural waste loads and the concentrations of micropollutants are high (Van Eck & De Rooij, 1993;Soetaert & Herman, 1995a,b;Zwolsman, 1999). From the 1980s on water quality has started to improve slowly, and this improvement continues in the 1990s (Van Damme et al, 1995;Van Eck et al, 1998).…”
Section: Introductionmentioning
confidence: 99%